General Facebook usage and its relationship to the accumulation of social capital. study on a sample of adolescents in Algiers - لعليجي محمد أمين (International Journal of Social Communication, 2023)
The aim of this study is to locate within the knowledge accumulation of social network sites in its relation to social ties. We aim to identify the relationship between the general usage of Facebook (psychological attachment/time spent/number of friends) with social capital (life satisfaction, self-esteem and social trust) on a sample of adolescents in Algiers, we emphasis on the deductive method to hypothesize that Facebook can be used as an on-line tool for generating off-line social capital. After testing the hypotheses, we have proven the relationship between the use of Facebook in its various dimensions (time spent on Facebook, the number of friends, in addition to his psychological attachment to use) and the accumulation of social capital among adolescents in Algiers.